The Relationship Between Rational Antibiotic Use and Theurapeutic Outcomes in Patients with Community Acquired Pneumonia - Fortuna, Tista Ayu; Nuraini, Filla Rizky; Karuniawati, Hidayah (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Pneumonia is an infection caused by microorganisms. Antibiotics are one of the treatments given to patients with pneumonia caused by bacterial infections. Rational use of antibiotics will prevent resistance. This study aims to determine the relationship between the rationality of antibiotic use and therapeutic outcomes in community-acquired pneumonia patients. We used a cross-sectional study and retrospectively collected data using purposive sampling. The inclusion criteria are non-ICU community pneumonia patients have complete medical record data, while the exclusion criteria are patients who died or had other infections. We evaluated the rationality of antibiotics using the Gyssens method. Based on the results, there are 240 patients, with 210 patients receiving rational therapy and 30 patients receiving irrational antibiotics. Based on the results, 6 patients did not receive antibiotics on time, 4 patients received the wrong dose, 2 patients did not get the correct interval, 16 patients received a dose that was too short, and 2 patients were prescribed alternative antibiotics that were more effective. The results of the analysis showed that there is a significant relationship between the rationality of antibiotic use and the therapeutic outcomes of community-acquired pneumonia patients (p-value < 0.001; OR 14.36).